Biodegradation of diethylketone by two fungi - Costa, Filomena (2014)
Two morphologically different fungi (one green and one white) from contaminated bioreactors with an aqueous solution of diethylketone and Streptococcus equisimilis were isolated and characterized at molecular level by sequencing the amplified ITS region. The ITS region sequence showed 99% match with Alternaria genera for the green fungi and 99% match with the Penicillium genera for the white fungi. The performance of these two fungi to biodegrade different concentrations of diethylketone from aqueous solutions was evaluated. The biodegradation of diethylketone was studied for an initial diethylketone concentration ranging from 0.5 to 4g/L in a batch mode of operation. The biodegradation rate found for both fungi followed the pseudo-second order kinetics for initial concentrations higher than 0.5 g/L and the resulting kinetic parameters are reported. The removal percentages obtained were approximately 100%, for all the initial concentrations tested.